Health-related quality of life and patient-reported outcomes of ofatumumab plus chlorambucil versus chlorambucil monotherapy in the COMPLEMENT 1 trial of patients with previously untreated CLL. (2nd October 2016) - Hillmen, Peter; Janssens, Ann; Babu, K. Govind; Kloczko, Janusz; Grosicki, Sebastian; Manson, Stephanie; McKeown, Astrid; Gupta, Ira; Chang, Chai-Ni; Offner, Fritz
Abstract: Background: Patients diagnosed with chronic lymphocytic leukemia (CLL) are usually elderly and frequently have a number of comorbidities. Health-related quality of life (HRQoL) for these patients is of utmost importance and should be taken into consideration when assessing new treatment options. The combination of ofatumumab with chlorambucil has shown longer progression-free survival compared with chlorambucil alone. In this study, we aim to assess how this treatment combination affects patients' health-related quality of life and patient-reported symptoms. Material and methods: In this open-label phase III trial, patients with previously untreated CLL for whom fludarabine-based treatment was contra-indicated, were randomized 1:1 to receive oral chlorambucil (10 mg/m 2 ) on Days 1–7 of a 28-day treatment cycle or to receive chlorambucil by this schedule plus intravenous ofatumumab (Cycle 1: 300 mg on Day 1 and 1000 mg on Day 8; subsequent cycles: 1000 mg Day 1) for 3–12 cycles. The EORTC QLQ-C30 and QLQ-CLL16 questionnaires were administered to patients before and during treatment, in follow-up and at the time of disease progression. The primary specified patient-reported outcomes were HRQoL and fatigue. Results: Patient-reported improvements from baseline in Global Health Status (GHS)/HRQoL scores and fatigue scores were recorded during treatment with both chlorambucil monotherapy and ofatumumab in combination with chlorambucil. There were no significant differences between the two treatment arms for GHS/HRQoL (p = 0.667) or fatigue (p = 0.103). Following treatment, numerical improvements to GHS/HRQoL and fatigue scores were reported, with no significant differences between the two treatment arms. Conclusion: Small but detectable improvements in patients' quality of life were reported as a result of treatment. The addition of ofatumumab to chlorambucil did not negatively impact HRQoL. Quality of life was maintained in the months following treatment.